Ethnobotanical study of medicinal plants in Adwa District, Central Zone of Tigray Regional State, Northern Ethiopia - Muhidin Tahir; Letebrhan Gebremichael; Tadesse Beyene; Patrick Van Damme (BMC, 2021)
Abstract Background Medicinal plants have been used for ages in Ethiopia. Some 887 plant species have been documented to heal human and livestock health problems. Documenting the traditional use of medicinal plants is a vital step in obtaining information on bioactive chemicals, preserving indigenous knowledge and ultimately interesting, medicinal plant species. We conducted this study with the aim of documenting the ethnobotanical knowledge associated with medicinal plant use in Adwa District, Northern Ethiopia. Methods The study was conducted from September 2018 to December 2019. A total of 393 informants (242 males and 151 females) were selected. Data were collected using semi-structured interviews, guided walks and group discussions. We calculated informant consensus factors (ICF) and fidelity level (FL) and performed ranking and paired comparisons. Data were analysed using descriptive statistics, including independent sample t test and ANOVA. Results Overall, we documented 127 medicinal plants belonging to 105 genera, under 54 families to be used by local people to address 43 human and 15 livestock ailments. Families Fabaceae and Solanaceae were the most important ones with 11 (8.66%) species each. Herbs were the dominant growth form (55 species), followed by shrubs (39). The most frequently used plant parts were leaves (24.27%) followed by roots (14%). The most important preparation method was crushing and pounding (42.7%) followed by fumigation (smoke and vapour) (23, 11.1%). The common route of administration was via skin application (67 or 32%) followed by oral (63, 27%). ICF showed that tonsillitis had the higher value (0.95). Cucumis ficifolius A. Rich. was the most preferred medicinal plant (36) treating abdominal pain, followed by Kalanchoe quartiniana A. Rich. for blackleg (34). Conclusions Adwa District is relatively rich in medicinal plant diversity and traditional knowledge on use, preparation and application of the medicinal flora. However, agricultural expansion (51%), overgrazing (43%) and drought (37%) were mentioned most when informants were asked about the threats to medicinal plants in Adwa District. Hence, on-site and off-site medicinal plant conservation would help protect medicinal plants in the district.